2012
DOI: 10.3390/toxins4090643
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immunohistochemical Analysis of Ochratoxin A Tumourigenesis in Rats and Urinary Tract Carcinoma in Humans; Mechanistic Significance of p-S6 Ribosomal Protein Expression

Abstract: Ochratoxin A (OTA) is considered to be a possible human urinary tract carcinogen, based largely on a rat model, but no molecular genetic changes in the rat carcinomas have yet been defined. The phosphorylated-S6 ribosomal protein is a marker indicating activity of the mammalian target of rapamycin, which is a serine/threonine kinase with a key role in protein biosynthesis, cell proliferation, transcription, cellular metabolism and apoptosis, while being functionally deregulated in cancer. To assess p-S6 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…It warrants further study that will provide new insights into the pathogenesis, biologic behaviour, and natural history of RCC. In the present context it is worth mentioning that even the most subtle morphological changes (easily missed on H&E stain) could be potentially spotted by ribosomal p-S6 protein immunohistochemical expression, as demonstrated by one of our previous studies [19]. Karyomegaly is presumed to result from nucleic acid replication without nuclear division.…”
Section: Discussionmentioning
confidence: 56%
“…It warrants further study that will provide new insights into the pathogenesis, biologic behaviour, and natural history of RCC. In the present context it is worth mentioning that even the most subtle morphological changes (easily missed on H&E stain) could be potentially spotted by ribosomal p-S6 protein immunohistochemical expression, as demonstrated by one of our previous studies [19]. Karyomegaly is presumed to result from nucleic acid replication without nuclear division.…”
Section: Discussionmentioning
confidence: 56%
“…With a vast number of OTA molecules necessary to pass though a kidney to generate a lone cell in the OSOM with a significant mutation, it is probably impossible to track its origin. However, the recognition of putative pre-neoplastic nephron fragments by immunohistochemical histology [ 10 ] points to a source of early malignancy from which transformed cells could be obtained for molecular genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, limited evidence of exposure is hardly predictive of toxicological outcome at the short and relatively high artificial OTA exposure, especially since no direct connection between adducts and the initiation of OTA- derived experimental renal cancer is yet available. That OTA is “a biologically plausible cause of testicular cancer in man” [ 32 ] seems premature since authors omit to cite both the consistently-negative rat and mouse evidence (e.g., [ 33 ]) and the immunohistochemical differentiation of tumour in testis and kidney in experimental OTA oncology in rats [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sangare-Tigori et al 58 reported higher OTA levels (17 to 204 μg/kg) in millet from the West African country of Côte d'Ivoire sampled between 1998 to 2002, which may be due to yearly variations in mycotoxin contamination patterns across the continent 55,56,59 . Exposure to OTA has been linked with nephropathy 60 , urinary tract tumors 61 and oxidative DNA damage leading to mutagenesis and eventually cancer 62 . Based on its carcinogenicity in animal studies, OTA has also been classified as a group 2B possible human carcinogen by the International Agency for Research on Cancer (IARC) 63 .…”
Section: Methods Validation and Comparative Evaluation Of Phwe And Solmentioning
confidence: 99%